Promising Detoxification Strategies to Mitigate Mycotoxins in Food and Feed - Zhou, Ting (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book is a printed edition of the Special Issue Promising Detoxification Strategies to Mitigate Mycotoxins in Food and Feed that was published in Toxins